A teatralidade no Festival Folclórico de Parintins: O jogo dos brincantes dos bois-bumbás - Bentes, Fabiano Baraúna (2018)
This project is a reflection, it is my walk, it is where I find myself, a new learning, a reading that navigates through knowledge and curiosities, around organicity and resignification. I connect in this research popular manifestations, play, theatricality and stories, of songs and charms, of myths and rites, of superstitions and passions, and specifically the passion of a people who dive in the folklore, splitting into colorful feelings, between red for Garantido and Blue for Caprichoso. Thus, I turn my attention to the intrinsic theatricality at the Parintins Folklore Festival and reflect on the theatrical act of the performances inside the arena, in the city and in the journey made by the Boi-Bumbás “brincantes“.